1992
DOI: 10.1021/ma00041a023
|View full text |Cite
|
Sign up to set email alerts
|

Structure-property comparison of sulfonated and carboxylated telechelic ionomers based on polyisoprene

Abstract: The structure and properties of polyisoprene-based telechelic ionomers having neutralized terminal sulfonate and carboxylate groups have been compared. In general, the mechanical properties of these materials suggest that metal sulfonates form stronger aggregates than the aggregates formed by metal carboxylates. This agrees with the results of previous workers who made similar comparisons for randomly substituted ionomers. Small-angle X-ray scattering data indicate that the periodic spacings between metal sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…Lundberg and Makowski6 showed that for a fixed level of functionality, the melt viscosities of the sulfonated ionomers were two to three orders of magnitude higher than those of the carboxylate analogs. Other investigations7–9 also observed similar differences in the properties of carboxylate and sulfonate ionomers. The differences are due to the fact that sulfonic acid (pK a ∼1) is a much stronger acid than carboxylic acid (pK a ∼4–5), which results in stronger electrostatic attractions between the sulfonate ion‐pairs than the carboxylate ion‐pairs.…”
Section: Introductionsupporting
confidence: 57%
“…Lundberg and Makowski6 showed that for a fixed level of functionality, the melt viscosities of the sulfonated ionomers were two to three orders of magnitude higher than those of the carboxylate analogs. Other investigations7–9 also observed similar differences in the properties of carboxylate and sulfonate ionomers. The differences are due to the fact that sulfonic acid (pK a ∼1) is a much stronger acid than carboxylic acid (pK a ∼4–5), which results in stronger electrostatic attractions between the sulfonate ion‐pairs than the carboxylate ion‐pairs.…”
Section: Introductionsupporting
confidence: 57%
“…At low elongations, the tensile strength of the two ionomers was superiour to that of IIR‐Acrylate‐XL, with Young's modulus values of 0.97 MPa for IIR‐BuImBr and 0.95 MPa for IIR‐VImBr‐XL, versus just 0.45 MPa for IIR‐Acrylate‐XL. This data demonstrates the ability of ionic aggregation at 25 °C to provide exceptional tensile strength, given that IIR‐BuImBr performed well while lacking a covalent network …”
Section: Resultsmentioning
confidence: 75%
“…Figure provides static modulus measurements recorded as a function of time for samples held at 100°C and a fixed shear strain. The non‐crosslinked polymers, IIR‐Acetate and IIR‐BuImBr, relaxed extensively, since they lacked the covalent network needed to prevent polymer chains from moving through their entanglements . The static modulus of IIR‐Acetate declined continuously, reaching zero stress in less than one minute.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the difficulty in synthesizing "matched" ionomers, this work still represents the only direct comparison of the melt rheology for randomly functionalized ionomers with different anion type; the conclusion that sulfonation yields stronger associations and higher viscosities (vs carboxylation) has become essentially axiomatic. 2,5,6 Recently, we 7 have applied Lundberg and Makowski's 4 sulfonation procedure to styrene-ethylenebutene (SEB) random terpolymers of narrow molecular weight distribution, synthesized by anionic polymeri-zation and catalytic hydrogenation; that work demonstrated and quantified the influence of both chain length and degree of sulfonation on the melt dynamics. 7 Lundberg and Makowski's parallel carboxylation procedure employed the complex between n-butyllithium (n-BuLi) and tetramethylethylenediamine (TMEDA) to lithiate the aromatic ring, 8 followed by reaction with CO 2 .…”
Section: Introductionmentioning
confidence: 99%